Design of a Novel Fault Tolerant XOR Structure in Quantum Dot Cellular Automata - Farnaz Shabani; Samira Sayedsalehi (Majlesi Journal of Electrical Engineering, 2024)
Quantum Cellular Automata (QCA) is one of the main substitutes for CMOS technology and it is used in implementation of different systems. Manifest features including high speed and low power consumption increase the subject of the QCA in research. However, the extensive possibility of occurrence of defects and appropriate physical implementation in the QCA is one of fundamental challenges in using such technology. In this study, basic details about nanotechnology and related discussions to the fault tolerant in this field are presented. In addition, by investigation on several XOR gates, two novel XOR gates are proposed, these gates were designed by using fault tolerance tile structures. Afterwards, for determining the optimum gate, the tolerance rate of these gates against missing cell defects were investigated. Simulation results showed that proposed gates have more tolerance against missing cell defects.